Physiotherapist-led treatment for young to middle-aged active adults with hip-related pain: consensus recommendations from the International Hip-related Pain Research Network, Zurich 2018. Issue 9 (15th November 2019) - Kemp, Joanne L; Risberg, May Arna; Mosler, Andrea; Harris-Hayes, Marcie; Serner, Andreas; Moksnes, Håvard; Bloom, Nancy; Crossley, Kay M; Gojanovic, Boris; Hunt, Michael A; Ishøi, Lasse; Mathieu, Nicolas; et al.
Abstract : The 1st International Hip-related Pain Research Network meeting discussed four prioritised themes concerning hip-related pain in young to middle-aged adults: (1) diagnosis and classification of hip-related pain; (2) patient-reported outcome measures for hip-related pain; (3) measurement of physical capacity for hip-related pain; (4) physiotherapist-led treatment for hip-related pain. Thirty-eight expert researchers and clinicians working in the field of hip-related pain attended the meeting. This manuscript relates to the theme of physiotherapist-led treatments for hip-related pain. A systematic review on the efficacy of physiotherapist-led interventions for hip-related pain (published separately) was conducted and found that strong evidence for physiotherapist-led treatments was lacking. Prior to the meeting, draft consensus recommendations for consideration in the meeting were also developed based on the systematic review. The draft consensus recommendations were presented to all of the meeting participants via email, at least 1 week prior to the meeting. At the meeting, these recommendations were discussed, revised and voted on. Six recommendations for clinical practice and five recommendations for research were included and all gained consensus. Recommendations for clinical practice were that (i) Exercise-based treatments are recommended for people with hip-related pain. (ii) Exercise-based treatment should be at least 3 months duration. (iii) Physiotherapist-led rehabilitation after hip surgery should be undertaken. (iv) Patient-reported outcome measures, measures of physical impairment and measures of psychosocial factors should be used to monitor response to treatment. (v) Physical activity (that may include sport) is recommended for people with hip-related pain. (vi) Clinicians should discuss patient expectations, use shared-decision making and provide education. Recommendations for research were (i) Reporting of exercise programmes: Exercise descriptors such as load magnitude, number of repetitions and sets, duration of whole programme, duration of contractile element of exercise, duration of one repetition, time under tension, rest between repetitions, range of motion through which the exercise is performed, and rest between exercise sessions should be reported. (ii) Research should investigate the optimal frequency, intensity, time, type, volume and progression of exercise therapy. (iii) Research should examine the effect of patient education in people with hip-related pain. (iv) Research should investigate the effect of other treatments used in people with hip-related pain (for example: manual therapy, medications, injections). (v) Research should examine the impact of comorbidities and social determinants on treatment effectiveness in people with hip-related pain. Clinicians and researchers working with young to middle-aged active adults with hip-related pain may use these consensus recommendations to guide, develop, test and implement individualised, evidence-based physiotherapist-led rehabilitation programmes.